The Influence of Arbuscular Mycorrhizal Fungi Inoculation on micro-propagated hybrid yam (Dioscorea spp.) growth and root knot nematode (Meloidogyne spp.) suppression - Tchabi, A.; Hountondji, F.C.C.; Ogunsola, B.; Lawouin, L.; Coyne, Danny L.; Wiemken, A.; Oehl, F. (Excellent Publishers, 2016)
The use of commercial inoculants containing non-indigenous arbuscular mycorrhizal fungi (AMF) is an emerging technology towards improving crop production in Africa. The present study aims at evaluating the influence of two strains of commercial arbuscular mycorrhizal fungi (AMF) products, based on Funneliformis mosseae and Glomus dussii, on yam growth and on root knot nematodes suppression. Using micropropagated plantlets two cultivars each of Dioscorea alata (TDa98-01183 and TDa98-165), and D. rotundata (TDr97-00551 and TDr 745) were inoculated with the F. mosseae and G. dussii products separately, at transplanting into 2L pots, and then inoculated one month later with 500 infective juveniles of Meloidogyne spp. and grown for further seven months in the greenhouse. Results demonstrated that even with low colonization rates (6%), AMF led to improved yam growth, especially for D. alata. When challenged with Meloidogyne spp., AMF inoculation significantly suppressed galling symptoms across the treatments and led to higher tuber yield. This study indicates the potential of AMF to sustainably improve yam quality and productivity, although further screening should be done in order to identify a suitable combination AMF species/strain x cultivar compatibility to optimise the results.